Pelatihan Dai Muda Profesional pada Mahasiswa Pendidikan Bahasa Arab Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi - Salman Hasani; Rofiazka Fahmi Huda; Warissuddin Soleh; Ady Muh. Zainul Musthofa; Jamil, Helmun (Politeknik Piksi Ganesha Indonesia, 2025)
This training aims to enhance the Arabic Language Education students skills at FKIP Universitas Jambi in professional preaching. The challenges of preaching today are increasingly complex, and young preachers are expected to convey Islamic messages effectively and relevantly. The training involved 30 students and included stages of preparation, socialization, training, mentoring, and evaluation. The materials covered public communication techniques, preaching strategies, and the use of digital media. During the training, students had the opportunity to practice directly in front of audiences and through social media. The result showed a significant improvement in communication skills, both in public delivery and in the use of digital preaching platforms. Additionally, students produced learning media such as tutorial videos and posters that can serve as aids in preaching activities. This activity also has the potential to enhance the quality of preaching in the community. With the skills acquired, it is hoped that students will become professional young preachers capable of positively contributing to the dissemination of Islamic values.